2012
DOI: 10.1007/s00421-012-2570-y
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nitric oxide and prostaglandins in the hyperemic response to a maximal metabolic stimulus: redundancy prevails

Abstract: Vasodilatory mechanisms controlling post-exercise or post-ischemic hyperemia are thought to be under redundant control and remain incompletely understood. A maximal metabolic stimulus evoked by ischemic exercise (IE) might limit redundancy by full activation of multiple pathways. We tested whether nitric oxide (NO) and/or prostaglandins contribute to the hyperemic response to IE. 17 subjects were randomized into two groups and performed three trials of IE during control (saline), N (G)-monomethyl-L-arginine (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…; Lopez et al . ). The strain gauge was placed around the non‐dominant forearm at its greatest circumference (∼5 cm below the antecubital crease), with the forearm positioned above heart level.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Lopez et al . ). The strain gauge was placed around the non‐dominant forearm at its greatest circumference (∼5 cm below the antecubital crease), with the forearm positioned above heart level.…”
Section: Methodsmentioning
confidence: 97%
“…; Lopez et al . ). Nevertheless, this vasodilatation appears to be driven in part by both endothelium‐derived NO and PGs, but there are conflicting reports on the extent to which postischaemic hyperaemic flow is affected by COX inhibition, with both increased and decreased flow being reported in young healthy adults (Kilbom & Wennmalm, ; Carlsson & Wennmalm, ; Carlsson et al .…”
Section: Introductionmentioning
confidence: 97%
“…FIGURE 19 shows analogous data from human forearm studies. In general, efforts to block multiple vasodilator pathways in skeletal muscle have demonstrated that the blood flow response to prolonged contractions is incredibly robust and difficult to reduce by more than ϳ20% under most circumstances (286,415). FIGURE 19 also demonstrates the critical importance of both the time resolution of the blood flow measurements in evaluating pharmacological approaches to blocking one or more dilator pathways and issues related to individual variability.…”
Section: P the Challenge Of Redundancymentioning
confidence: 99%
“…But brachial artery dilation is mediated by shear receptors which activate through microvilli and a prostaglandin mediated process including the release of nitric oxide [4446]. The local response to occlusion is not mediated by prostaglandins or nitric oxide [47]. The micro vascular response to heat is mediated by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%